2012
DOI: 10.3748/wjg.v18.i35.4934
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of hyperlipidemia and acute cerebral ischemia/reperfusion induces severe liver damage in a rat model

Abstract: The coexistence of HL and acute cerebral I/R induces severe liver damage, suggesting that cerebral ischemic stroke would exaggerate the damage of liver caused by HL. This effect is possibly due to enhanced CYP2E1 induction which further promotes oxidative damage, inflammation and hepatocyte apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…This is consistent with a previous study showed that body weight gain was not affected by HFD in gerbils, although HFD was shown to result in higher hepatic vitamin A stores and lower hepatic b-carotene stores [31]. On the other hand, hyperlipidemia, a condition with high plasma levels of triglyceride and cholesterol, is associated with links to the increased incidence of stroke [32,33]. Hyperlipidemia induced by HFD is a highly prevalent condition in ischemic stroke patients, although it per se is not a direct predictor of ischemic stroke [32] We were aware that these results, epically in body weight, were inconsistent with other studies, which showed that HFD induced obesity and increased body weight in experimental animals [10,20,34].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with a previous study showed that body weight gain was not affected by HFD in gerbils, although HFD was shown to result in higher hepatic vitamin A stores and lower hepatic b-carotene stores [31]. On the other hand, hyperlipidemia, a condition with high plasma levels of triglyceride and cholesterol, is associated with links to the increased incidence of stroke [32,33]. Hyperlipidemia induced by HFD is a highly prevalent condition in ischemic stroke patients, although it per se is not a direct predictor of ischemic stroke [32] We were aware that these results, epically in body weight, were inconsistent with other studies, which showed that HFD induced obesity and increased body weight in experimental animals [10,20,34].…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, hyperlipidemia, a condition with high plasma levels of triglyceride and cholesterol, is associated with links to the increased incidence of stroke [32,33]. Hyperlipidemia induced by HFD is a highly prevalent condition in ischemic stroke patients, although it per se is not a direct predictor of ischemic stroke [32] We were aware that these results, epically in body weight, were inconsistent with other studies, which showed that HFD induced obesity and increased body weight in experimental animals [10,20,34]. These differences may be due to the age of animals, experimental models and/or methods used in their experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlipidemia is characterized by increased TC, TG, and LDL-C levels and by decreased HDL-C levels, and is considered to be one of the major risk factors for liver cirrhosis, hepatocellular carcinoma, and liver failure [19]. Although statins, also known as 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitors, are effective therapies for reducing serum LDL-C levels, they also induce adverse side effects including muscle myopathy and derangements in hepatic function [20].…”
Section: Discussionmentioning
confidence: 99%
“…Serum triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C) were detected by Beckman Coulter synchron LX20 autoanalyzer (Beckman Coulter Inc., United States). The animals with serum TC level >3.87 mmol/L were considered as HL rats and included in the study (Gong et al 2012). Subsequently, normal diet group (fed control diet) and HFD group (HL rat) were, respectively, divided into two subgroups: sham, HL, I/R or HL + I/R group (Fig.…”
Section: Experiments Designmentioning
confidence: 99%